2015
DOI: 10.1080/02508060.2015.1025196
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of water management in coastal Bangladesh: from temporary earthen embankments to depoliticized community-managed polders

Abstract: This article examines the historical evolution of participatory water management in coastal Bangladesh. Three major shifts are identified: first, from indigenous local systems managed by landlords to centralized government agencies in the 1960s; second, from top-down engineering solutions to small-scale projects and people’s participation in the 1970s and 1980s; and third, towards depoliticized community-based water management since the 1990s. While donor requirements for community participation in water proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 20 publications
1
80
1
Order By: Relevance
“…The recent notion of participation has been even deeper and includes gender and equity dimensions of participation. In contrast to the above findings, some recent studies (e.g., [40,41]) found that true participation is not happening at field level.…”
Section: Evaluation Of Project-level Transformationscontrasting
confidence: 46%
“…The recent notion of participation has been even deeper and includes gender and equity dimensions of participation. In contrast to the above findings, some recent studies (e.g., [40,41]) found that true participation is not happening at field level.…”
Section: Evaluation Of Project-level Transformationscontrasting
confidence: 46%
“…Such dynamic physical and anthropogenic process (de Die, 2013;van Staveren et al, 2016) are also linked with the historic evolution of water management practices from temporary earthen embankments to depoliticized community-based water management (Dewan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Upstream water withdrawal and the G-K irrigation project have consequently increased water salinity (Gain et al, 2007;) and induced high rates of sediment deposition in the south west coastal region. In parallel, coastal polders (earthen embankments) have been constructed since the 1960s in order to provide protection from floods and to increase agricultural production However, these polders have prevented silt from the rivers from being deposited on flood plains, resulting in high rates of sedimentation on the river bed, congesting both rivers and canals and causing many to dry out over a period of decades (Dewan et al, 2014;Dewan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency comparisons between CBM and traditional models often found that CBM can resolve issues effectively with less burden on other taxpayers [34][35][36]. Employing CBM as a tool for resource management has been found in the fields of water resource management [37,38], forest management [39,40], community services [41,42], etc.…”
Section: Community-based Mswmmentioning
confidence: 99%